Exploring precision treatments in immune‐mediated inflammatory diseases: Harnessing the infinite potential of nucleic acid delivery - Lingxiao Xu; Zhenxuan Shao; Xia Fang; Zengfeng Xin; Shenzhi Zhao; Hongbo Zhang; Yu Zhang; Wenbiao Zheng; Xiaohua Yu; Zengjie Zhang; Lingling Sun (Exploration)
Abstract Immune‐mediated inflammatory diseases (IMIDs) impose an immeasurable burden on individuals and society. While the conventional use of immunosuppressants and disease‐modifying drugs has provided partial relief and control, their inevitable side effects and limited efficacy cast a shadow over finding a cure. Promising nucleic acid drugs have shown the potential to exert precise effects at the molecular level, with different classes of nucleic acids having regulatory functions through varying mechanisms. For the better delivery of nucleic acids, safe and effective viral vectors and non‐viral delivery systems (including liposomes, polymers, etc.) have been intensively explored. Herein, after describing a range of nucleic acid categories and vectors, we focus on the application of therapeutic nucleic acid delivery in various IMIDs, including rheumatoid arthritis, inflammatory bowel disease, psoriasis, multiple sclerosis, asthma, ankylosing spondylitis, systemic lupus erythematosus, and uveitis. Molecules implicated in inflammation and immune dysregulation are abnormally expressed in a series of IMIDs, and their meticulous modulation through nucleic acid therapy results in varying degrees of remission and improvement of these diseases. By synthesizing findings centered on specific molecular targets, this review delivers a systematic elucidation and perspective towards advancing and utilization of nucleic acid therapeutics for managing IMIDs.